Stochastically multimerized ParB orchestrates DNA assembly as unveiled by single-molecule analysis. Issue 16 (29th July 2022) - Guo, Lijuan; Zhao, Yilin; Zhang, Qian; Feng, Ying; Bi, Lulu; Zhang, Xia; Wang, Teng; Liu, Cong; Ma, Hanhui; Sun, Bo
Abstract: The tripartite ParAB S system mediates chromosome segregation in a wide range of bacteria. Dimeric ParB was proposed to nucleate on parS sites and spread to neighboring DNA. However, how properly distributed ParB dimers further compact chromosomal DNA into a higher-order nucleoprotein complex for partitioning remains poorly understood. Here, using a single-molecule approach, we show that tens of Bacillus subtilis ParB (Spo0J) proteins can stochastically multimerize on and stably bind to nonspecific DNA. The introduction of CTP promotes the formation and diffusion of the multimeric ParB along DNA, offering an opportunity for ParB proteins to further forgather and cluster. Intriguingly, ParB multimers can recognize parS motifs and are more inclined to remain immobile on them. Importantly, the ParB multimer features distinct capabilities of not only bridging two independent DNA molecules but also mediating their transportation, both of which are enhanced by the presence of either CTP or parS in the DNA. These findings shed new light on ParB dynamics in self-multimerization and DNA organization and help to better comprehend the assembly of the ParB-DNA partition complex.